IN HER OWN WORDS: THE SEMANTICS OF FEMALE AUTHORSHIP IN ANCIENT GREECE, FROM SAPPHO TO NOSSIS1. (28th December 2016) - Hauser, Emily
Abstract : What we call things is important—it reveals what we think about the world. What we call ourselves, however, is even more important. It reveals ideas and assumptions about identity, gender, community. It helps us to see where we fit in in society; what we understand our purpose, our role to be; the kinds of activities we undertake. In a history where women have been largely barred from higher-paying, traditionally male occupations, the way in which women in particular use terminology to lay claim to skills and expertise in counterpoint to a generally male-dominant culture speaks volumes about the ways in which women see themselves and their relationship to their work. As Erica Jong puts it in her feminist essay, The Artist as Housewife, 'naming is a form of self-creation'.